2015
DOI: 10.3389/fmicb.2015.00580
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms for the evolution of bacterial morphologies and growth modes

Abstract: Bacteria exhibit a rich diversity of morphologies. Within this diversity, there is a uniformity of shape for each species that is replicated faithfully each generation, suggesting that bacterial shape is as selectable as any other biochemical adaptation. We describe the spatiotemporal mechanisms that target peptidoglycan synthesis to different subcellular zones to generate the rod-shape of model organisms Escherichia coli and Bacillus subtilis. We then demonstrate, using the related genera Caulobacter and Asti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 130 publications
(169 reference statements)
1
65
0
5
Order By: Relevance
“…This bacterium lacks both MinCD and NO systems to regulate the placement of the FtsZ ring. Instead it employs a ParA-like ATPase MipZ ( Mi dcell p ositioning of Fts Z ) to regulate the assembly site of the Z-ring (34, 111, 129). MipZ forms a gradient by interacting directly with origin-proximal DNA-bound ParB- parS complexes at the flagellated (stalked) pole prior to cell division and translocating with the newly replicated origin to the non-flagellated pole (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium lacks both MinCD and NO systems to regulate the placement of the FtsZ ring. Instead it employs a ParA-like ATPase MipZ ( Mi dcell p ositioning of Fts Z ) to regulate the assembly site of the Z-ring (34, 111, 129). MipZ forms a gradient by interacting directly with origin-proximal DNA-bound ParB- parS complexes at the flagellated (stalked) pole prior to cell division and translocating with the newly replicated origin to the non-flagellated pole (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, much research in the bacterial morphology field focuses on defining the mechanisms by which the cell wall is synthesized and modified to produce different cell body shapes. We refer the reader to several excellent reviews on cell wall synthesis and the evolution of bacterial morphogenesis for an in-depth consideration of this topic (6)(7)(8)(9). To summarize, studies in a variety of organisms have revealed that cell shape can be derived from asymmetric positioning of new cell wall synthesis, alteration of cell wall thickness, and/or changes in the chemical composition of the cell wall polymer or its extent of cross-linking.…”
Section: Cell Body Morphologymentioning
confidence: 99%
“…eptidoglycan (PG) biosynthesis and placement are dynamic processes that determine the shapes, sizes, chaining, and resistance to turgor of bacterial cells (1)(2)(3)(4)(5)(6). In Gram-positive bacteria, PG also serves as the scaffolding for covalent attachment of surface wall teichoic acid, capsule, and sortase-attached proteins (7)(8)(9).…”
mentioning
confidence: 99%